2021
DOI: 10.17509/jpjo.v6i1.30126
|View full text |Cite
|
Sign up to set email alerts
|

Kepemimpinan dan Performa Bermain Bola Tangan melalui Model Pendidikan Olahraga

Abstract: The implementation of sports activities and learning is carried out to improve performance. The meaning of the values of sports, as the most important thing of positive sports development, has not been sufficiently revealed. The purpose of this study was to determine the differences in the development and mastery of the students through the implementation of sport education models containing leadership content and without leadership content. This study used a quasi-experimental control group pre-post test desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Overall, that Sport Education can be used in learning for students at high-field sports colleges is in line with previous research that uses Sports Education in learning at high-field sports colleges which has a positive impact Ginanjar, Mubarok, et al, 2021a;Ginanjar, Ramadhan, Effendy, Kharisma, & Agustin, 2023;Purwanto, Susanto, & Pahalawidi, 2014;Slamet, 2018;Slamet et al, 2021;Solihin, Ginanjar, & Budiman, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, that Sport Education can be used in learning for students at high-field sports colleges is in line with previous research that uses Sports Education in learning at high-field sports colleges which has a positive impact Ginanjar, Mubarok, et al, 2021a;Ginanjar, Ramadhan, Effendy, Kharisma, & Agustin, 2023;Purwanto, Susanto, & Pahalawidi, 2014;Slamet, 2018;Slamet et al, 2021;Solihin, Ginanjar, & Budiman, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…The research instrument used the ILI-SF research results (Steffens et al, 2014) which were also corroborated by the research results (Slamet et al, 2021) but the instrument has not been validated. ILI-SF consists of four dimensions, namely: prototypicality, improvement, entrepreneurship, and impresario, each dimension consisting of 1 test item (see Figure 1).…”
Section: Study Organizationmentioning
confidence: 88%
See 1 more Smart Citation
“…Then, there is a link between OBE and the MBKM curriculum and there is also a link between OBE and the implementation of SE in sports study programs (Ginanjar et al, 2022). Furthermore, it is recommended that SE at the HE level be better used as a basis for the curriculum of programs, especially those related to sports, in learning that uses various sports as a strategy in teaching and SE also deserves attention to be developed, by stakeholders in schools and other institutions (Slamet, Yudiana, Mahendra, & Ma'mun, 2021). Then, SE learning is more oriented towards the student center where students play a more active role in the learning process (Kurnia & Hidayat, 2021;Kurniawan & Suherman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the decades since the first trials of sport education, extensive evidence has shown that the model's effectiveness in producing competent, literature and enthusiastic sports players is unaffected by location, sport content, and sport culture (Bessa et al, 2021;Hastie & Wallhead, 2016). For example, within Indonesia, the model has had a positive impact on students' motivation (Ramadhan & Effendy, 2021), game performance and leadership (Slamet et al, 2021), as well as promotion a more goaloriented approach to sport (Ginanjar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%